2011
DOI: 10.1073/pnas.1104047108
|View full text |Cite
|
Sign up to set email alerts
|

Value-driven attentional capture

Abstract: Attention selects which aspects of sensory input are brought to awareness. To promote survival and well-being, attention prioritizes stimuli both voluntarily, according to context-specific goals (e.g., searching for car keys), and involuntarily, through attentional capture driven by physical salience (e.g., looking toward a sudden noise). Valuable stimuli strongly modulate voluntary attention allocation, but there is little evidence that high-value but contextually irrelevant stimuli capture attention as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

137
1,350
29
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 985 publications
(1,578 citation statements)
references
References 47 publications
137
1,350
29
3
Order By: Relevance
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More specifically, we demonstrated that stimuli associated with primary reward can involuntary orient spatial attention and that this modulation critically depends on the properties of the primary reward. These results are consistent with recent experiments testing the incentive salience hypothesis in humans, and showing involuntary attentional interference effects by rewardassociated cue (Anderson et al, 2011a(Anderson et al, , 2011bHickey & van Zoest, 2012;Hickey et al, 2010aHickey et al, , 2010bHickey et al, , 2011. Critically, our results also revealed that this attentional capture is independent of the stimuli's low-level perceptual characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis has recently been tested in humans (Anderson, Laurent, & Yantis, 2011a, 2011bHickey, Chelazzi, & Theeuwes, 2010a, 2010b, 2011. In Anderson et al (2011aAnderson et al ( ), (2011b, a simple visual stimulus (i.e., a one-color shape) was associated with a secondary reward (i.e., a visual monetary symbol).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that distractor effects, such as the one observed here, appear to emerge outside of volitional control. In combination with previous findings showing an effect of prior learning on the ability of distractors to cause interference (Anderson, Laurent, & Yantis, 2011a, 2011bDella Libera & Chelazzi, 2009;Le Pelley, Vadillo, & Luque, 2013), this finding suggests that learning can influence the properties of the bottom-up processing of a stimulus to the extent that its ability to compete for attention is affected. This is an idea further clarified in later stages of this chapter.…”
Section: The Attentional Blink As An Index Of Automaticitysupporting
confidence: 76%
“…Subsequent work has replicated this basic effect under a number of conditions (Anderson et al, 2011b;Hickey, Chelazzi, & Theeuwes, 2010a;2011;Le Pelley, Pearson, Griffiths, & Beesley, 2015).…”
Section: Learning To Attend: Effects Of Predictiveness On Perceptionmentioning
confidence: 83%